(untitled) (Journal of Applied Oral Science, 2022)
Objectives: To evaluate the influence of photobiomodulation with infrared laser (IRL) in the rat pulp tissue after bleaching, considering the immunolabeling of interleukin (IL)-23 and hypoxia-inducible factor (HIF)-1α. Methodology: The right and left molars of forty rats were divided into groups: Control – with placebo gel and Bleached – with 35% hydrogen peroxide (H2O2). Half of the rats received one IRL application on both sides, establishing a split-mouth design, which resulted in 4 groups with 20 hemi-maxillae each: Control, Bleach, IRL, and Bleached-IRL. Rats (n=10) from each group were euthanized, at 2- and 30-days mark, and the pulp tissue was evaluated using inflammation and immunolabeling scores. Wilcoxon and Mann-Whitney statistical tests were performed (p<0.05). Results: At the 2-days mark, the Bleached group had severe inflammation and necrosis in the occlusal thirds of the pulp, and moderate to severe inflammation in cervical third, whereas the Bleached-IRL had mild to moderate inflammation (p<0.05). At the 30-days mark, there was no inflammation, but tertiary dentine formation in the bleached groups. Regarding IL-23, severe immunolabeling was observed in the Bleached group (p<0.05) at the 2-days mark; at the 30-days mark, there was a reduction in immunolabeling, in which the Bleached group had moderate and the Bleached-IRL group had mild immunolabeling (p>0.05). HIF-1α was more evident at the 2-days mark in the Bleached group, without significant difference with the Bleached-IRL (p>0.05). The difference was observed between the bleached and control groups, without immunolabeling (p<0.05); at the 30-days mark, the Bleached group had reduction in HIF-1α immunolabeling, while the Bleached-IRL had an increase; the difference remained between the bleached and the controls groups (p<0.05). Conclusion: Photobiomodulation using IRL minimized the inflammation and IL-23 immunolabeling in the pulp tissue of rats after dental bleaching, but did not influence significantly the HIF-1α immunolabeling.